The Modernization of Laughter in Costa Rica: Jiménez and Marín Cañas - Ramírez Villalobos, Grethel (2020)
The relationships between humor and modern literature are examined based on two Costa Rican novelists of the early twentieth century: Max Jiménez and José Marín Cañas. In Unos fantoches and Tú, la imposible, the use of cynical laughter and irony is a means for the artistic analysis of social degradation and the crisis of modern man. Due to their esthetic-ideological orientation, these novels implied a renewal of Costa Rican literature, fueled by contact with avant-garde historical movements and the modern esthetics of literary humor.